2007
DOI: 10.1016/j.bbapap.2007.03.007
|View full text |Cite
|
Sign up to set email alerts
|

NMR solution structure of the angiostatic peptide anginex

Abstract: Anginex, a designed peptide 33mer, is known to function both as an antiangiogenic and bactericidal agent. Solving the NMR solution structure of the peptide is key to understand better its structureactivity relationships and to design more bioactive peptides and peptide mimetics. However, structure elucidation of anginex has been elusive due to subunit exchange-induced resonance broadening. Here, we found that performing NMR structural studies in a micellar environment abolishes exchange broadening and allows t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 30 publications
2
28
0
Order By: Relevance
“…Having established anginex as a potent antiangiogenic and antitumor agent, we used the folded structure of anginex [28,29] to design a small library of calix [4]arene-scaffold protein surface topomimetics that embodied the molecular dimensions, surface topology, and overall chemical composition of the peptide. From screening of this library, we demonstrated that topomimetic 0118 was also a potent angiogenesis inhibitor in vitro, as well as in vivo [30].…”
Section: Introductionmentioning
confidence: 99%
“…Having established anginex as a potent antiangiogenic and antitumor agent, we used the folded structure of anginex [28,29] to design a small library of calix [4]arene-scaffold protein surface topomimetics that embodied the molecular dimensions, surface topology, and overall chemical composition of the peptide. From screening of this library, we demonstrated that topomimetic 0118 was also a potent angiogenesis inhibitor in vitro, as well as in vivo [30].…”
Section: Introductionmentioning
confidence: 99%
“…6DBF7, which is about onethird the mass of anginex, was shown to inhibit tumor growth in mice better than parent anginex. Although both anginex and 6DBF7 share the same spatial arrangements of functionally important amino acid residues in the context of antiparallel b-sheet structure (Dings et al, 2003a;Mayo et al, 2003;Arroyo and Mayo, 2007), it was unknown whether 6DBF7 targeted gal-1 similar to anginex. The previous results demonstrate that the DBF-based peptidomimetic indeed targets gal-1.…”
Section: Discussionmentioning
confidence: 99%
“…148 High resolution structure of anginex was determined at 1 mM peptide concentration in a H2O:DMSO 1:1 mixture, pH 5.5 and 40˘C after addition of 50 mM DPC. 110 In our hand, these conditions did not result in reasonable spectra.…”
Section: Conformation At the Residue Level By Nmr Optimization Of Meamentioning
confidence: 66%
“…We found values around zero for the first strand indicating random conformation in line with the earlier observation that the first strand of the -sheet was more flexible than the other two. 110 Generally, SSP values were lower than that of the parent peptide, all  3 substitutions resulted in induced helical propensity in the first strand, which could be explained by the helix promoting tendencies of these building blocks and the flexibility of this segment. These suggested that the amino acid replacements had a strong effect on the secondary structure propensity of an entire chain segment.…”
Section: Secondary Structure Propensitymentioning
confidence: 89%
See 1 more Smart Citation